Bedah Menoreh tourism infrastructure development policy and its challenges in encouraging economic growth of the local community - Ebtana Sella Mayang Fitri; Ridho Gata Wijaya (Jurnal Pariwisata Pesona, 2022)
Borobudur is one of the New Bali sites that has had a significant impact on the tourism industry as well as infrastructure development. The opening of the Yogyakarta International Airport is one of the driving factors. The existence of YIA Airport is intended to be able to connect directly with Borobudur Temple. Therefore, good access is required by establishing the Bedah Menoreh route as the primary tourism route. The focus of infrastructure development is to encourage the economy of the local people in four different sub-districts. The Menoreh route, on the other hand, has allowed investors to engage in the development of tourism in the area. By monitoring the statistics and some facts that occur in the field, this article explores the development policy of Bedah Menoreh's tourism infrastructure and its difficulties in the local community's economic development. A qualitative method was utilized, including secondary data sources in the form of linked policies and reports from diverse sources. The purpose of this paper is to identify the projected Bedah Menoreh infrastructure development program and determine whether it is in conformity with the government's objectives for boosting the local economy. This article concludes that the development of the Bedah Menoreh Route as a supporter of tourism infrastructure is a good idea, but determining policies also requires synergy with the local community in order to have a positive impact on welfare in terms of economic, social, cultural, and environmental aspects.